The Effect of School Principals' Academic Supervision and Teachers' Professional Competence on The Quality of Learning in Elementary Schools - Listiyanto, Hery; Kusumaningsih, Widya; Sulianto, Joko (JURNAL AL-TANZIM, 2026)
This study aims to analyze the influence of principals' academic supervision and teachers' professional competence on the quality of learning in elementary schools. Using a quantitative approach and a survey of 138 teachers, data were collected via a Likert-scale questionnaire and analyzed using simple and multiple linear regression in SPSS version 29. The results showed that principals' academic supervision had a positive and significant effect on the quality of learning (r = 0.520; contribution 27%). Teachers' professional competence also had a positive and significant effect, with a correlation coefficient (r = 0.733) and a coefficient of determination (R² = 0.538), accounting for 53.8% of the variation in learning quality (p < 0.001). Together, academic supervision and teachers' professional competence explained 70% of the variation in learning quality (R² = 0.700; Adjusted R² = 0.695). This regression model was significant (F = 32.879; p < 0.001), indicating that both independent variables explained 70% of the variance in learning quality. These findings suggest that improving academic supervision and strengthening teachers' professional competencies can improve the quality of learning in elementary schools.